Kinetics of fenthion excretion in milk following a topical application in two breeds of dairy cattle - Ramírez, Nicolás; Ruiz B., Jhon D.; Restrepo, Luis F.; López, Carlos A. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The mammary excretion of fenthion was determined in cross-bred (Bon x Holstein) and pure Holstein cows following a topical (pour-on) application of a commercial formulation. Two groups of five cows each received a single application at the recommended dosage of 10 mg/kg BW on the withers. Milk samples were collected twice a day, from the morning and afternoon milkings during a 5-day period and analyzed for fenthion and total fat contents. A bi-compartmental analysis was used to describe the pharmacokinetic parameters. Overall fenthion milk concentrations increased progressively to reach maximum peaks (Cmax) of 0.4 ppm and 0.2 ppm at about 33 hr post-treatment in cross-bred and pure Holstein cows, respectively. However, since total residues in milk were strongly correlated with total fat content, for any particular day the concentrations attained in the morning milking were lower than those for the afternoon collection. The elimination half-lives (T1/2) for the two cattle breeds were 52.5 and 59.3 hr for cross-bred and Holstein respectively as indicated by milk concentrations. Fenthion concentrations declined to the maximum residue limit of 0.05 ppm set by the OMS FAO at 8.0, and 6.61 days post application, in cross-bred and pure bred Holstein cows respectively. These results suggest that withdrawal time for milk from lactating dairy cows treated with topical fenthion, could be of 8 days approximately.